Which Strategy is the Best Practice for Environmental Tourism Impact in Thailand? - Kitisripanya, Nonnaporn; Pongkonglad, Siriporn (วารสารเพื่อการพัฒนาการท่องเที่ยวสู่ความยั่งยืน, 2019)
This study aims to identify strategies to manage tourist destinations of Thailand into a sustainable way focused on environmental aspects. Firstly, the author reviews environmental tourism impact in Thailand which has occurred to degrade tourist destinations. It has been evidenced that garbage disposal becomes the most significant problem which Thailand is faced while it is a challenge for tourism income. Various strategies which tourism management planner applied to reduce the impact are raised to enhance environmental sustainable tourism, however the writer proposes Education and Communication Theory, Stakeholders’ Involvement, Payment for Ecosystem Services, Social Network by Facebook, and a campaign by Tourism Authority of Thailand. Furthermore, Thailand has limit in social, cultural, and geological features. It is concluded that there is no single strategy to combat or encounter with the problem, however we also need the right policy decision making to solve all the problems, or to determine which is the best suit for Thailand tourism impacts in any dimensions.